The Image of The Folk Hero in The Novels by V. Shukshin And Kh. Tukhtabaev: A Comparative Analysis (Based on I Have Come to Give You Freedom and The Golden Head of The Avenger) - Dzhagaspanyan Rafik Nikolaevich (International Journal Of Literature And Languages, 2026)
Problem. The comparative study of historical prose in Russian and Uzbek literary traditions has remained underdeveloped, with each scholarly community analyzing folk hero narratives in isolation. No cross-cultural inquiry has determined how writers working within distinct aesthetic and historical circumstances construct the same character type: the popular rebel who becomes a symbol of justice. Aim. This article conducts a comparative analysis of the folk hero archetype in Vasiliy Shukshin’s I Have Come to Give You Freedom, centered on Stepan Razin, and Khudoyberdi Tukhtabaev’s The Golden Head of the Avenger, centered on Namaz, identifying typological convergences and culturally specific divergences. Results. The analysis establishes that both novelists construct their protagonists upon a shared typological foundation: the hero’s bond with the oppressed, the trajectory from personal grievance to collective rebellion, the interweaving of chronicle and legend, and a tragic denouement converting the individual into a mythic symbol. Simultaneously, Shukshin’s Razin is shaped by existential introspection and the Russian skaz tradition, while Tukhtabaev’s Namaz reflects the Central Asian doston heritage and an Islamic moral universe. The proposed model offers a replicable framework for cross-cultural comparisons of folk hero narratives in post-Soviet literatures.